How civilian casualty information shapes support for US involvement in an ally country’s war effort - Alon P. Kraitzman; Tom W. Etienne; Dolores Albarracin (Humanities & Social Sciences Communications)
Abstract War is often described as “heart-wrenching,” but how do portrayals of conflict influence public support for US involvement when it is not directly engaged? This paper examines how information about civilian casualties and infrastructural damage, commonly found in media coverage, shapes public opinion on whether the US should provide military, diplomatic, and economic aid to foreign nations. Using a longitudinal survey of a probability sample of Americans and four experiments (three preregistered and two with nationally representative samples), we analyze both the ongoing conflict between Ukraine and Russia and hypothetical conflicts involving a US ally and a US adversary. Findings indicate that information about civilian harm significantly increases public support for US involvement, with empathy mediating this effect-but only when the casualties are civilians from an ally, not an adversary, country. The theoretical and applied implications of these important and timely findings are discussed.